2019
DOI: 10.1002/jlb.3hi1119-389rrrr
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Ly6C+ monocytes/macrophages contributes to their accumulation in mouse skin wounds

Abstract: Monocytes and macrophages (Mo/MΦ) play critical roles in all phases of skin wound healing. The majority of these cells are thought to be recruited from blood Mo; however, the role local proliferation of Mo/MΦ in the wound has not been defined. Therefore, we tested the hypothesis that local proliferation of Mo and/or MΦ contributes to their accumulation during wound healing. Male C57Bl/6 mice (N = 4–9/group) were subjected to excisional skin wounding. Proliferating Mo/MΦ (F4/80+Ki67+) were observed in wound cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
5
24
0
Order By: Relevance
“…After infiltrating wounds, novel recent findings demonstrate that inflammatory Mo/Mϕ (Ly6C hi F4/80 –/lo ) proliferate rapidly peaking on day 6 post-wounding. In contrast, the majority of mature wound Mϕ (Ly6C – F4/80 + ) remain at resting G0 phase indicating that proliferation of infiltrating inflammatory Mo followed by their differentiation into mature Mϕ results in wound Mϕ expansion ( Pang et al, 2019 ). In addition, several studies have demonstrated that bone marrow-derived Mo contribute to skin wound Mϕ and that similar to other tissue injuries such as myocardial infarction and hindlimb ischemia, skin wounding also promotes bone marrow monopoiesis in mice ( Ishida et al, 2008 ; Sager et al, 2015 ; Fang et al, 2018 ; Barman et al, 2019a ).…”
Section: Origin Of Skin Wound Mϕmentioning
confidence: 99%
“…After infiltrating wounds, novel recent findings demonstrate that inflammatory Mo/Mϕ (Ly6C hi F4/80 –/lo ) proliferate rapidly peaking on day 6 post-wounding. In contrast, the majority of mature wound Mϕ (Ly6C – F4/80 + ) remain at resting G0 phase indicating that proliferation of infiltrating inflammatory Mo followed by their differentiation into mature Mϕ results in wound Mϕ expansion ( Pang et al, 2019 ). In addition, several studies have demonstrated that bone marrow-derived Mo contribute to skin wound Mϕ and that similar to other tissue injuries such as myocardial infarction and hindlimb ischemia, skin wounding also promotes bone marrow monopoiesis in mice ( Ishida et al, 2008 ; Sager et al, 2015 ; Fang et al, 2018 ; Barman et al, 2019a ).…”
Section: Origin Of Skin Wound Mϕmentioning
confidence: 99%
“…Countering this view, Pang et al. show that Ly6C‐expressing myeloid cells recruited to the site of an excisional skin wound undergo extensive proliferation 6 . These findings complement two recent studies that found urinary tract 7 and hepatic 8 monocytes to proliferate during bacterial and helminth infection, respectively, suggesting bone marrow‐derived monocytes are able to proliferate to a significant degree within certain inflamed tissues.…”
Section: Figurementioning
confidence: 70%
“…Factors in the local wound environment stimulate these bone marrow-derived monocytes to differentiate into macrophages and the precise combination of these factors is what appears to dictate macrophage phenotype, although the original phenotype of the bone marrow monocytes may also dictate the macrophage phenotype. In addition, some immune cells can proliferate in the wound [ 39 ]. It is the inflammatory monocytes/macrophages derived from the circulating monocytes, but not the mature wound macrophages, that are able to proliferate in the wound and, at the mid-stages of healing, these cells constitute around 25% of macrophage population.…”
Section: The Inflammatory Phase Of Wound Healing and Macrophagesmentioning
confidence: 99%